EMPIRICAL ANALYSIS ON THE EFFECTS OF OPENING UP ON ECONOMIC GROWTH IN ALGERIAN RURAL STEPPIQUE AREAS - Djamal, Dahmane; komi Apedo, Atchemdi; Habib, Guessas (The journal of contemporary issues in business and government, 2024)
This study aims to highlight the causal relationship between Infrastructure for opening up and economic growth in the municipality of Ksar Chellala in Algeria, which benefited from infrastructure development programs to combat its spatial and social isolation. By adopting an econometric approach based on the Cobb-Douglas production function over the period (2000-2020), the results showed that infrastructure for opening up triggered an increase in production through the strong direct causal link. Telecommunications have far impacted it, because its elasticity of 1% led to an increase of 0.93%, while they are around 0.65% for roads and electricity. The conclusions call for the continuation of operations and to give as much attention to their quality, their maintenance as well as their bioeconomic benefits.